New functional tissues induced by a galling lepidopteran on stems of Marcetia taxifolia (Melastomataceae): An analysis based on cell wall composition and dynamics - Ferreira, Bruno G.; Oliveira, Denis C.; Isaias, Rosy M. S. (Acta Botânica Brasílica, 2025)
Abstract The plant cell walls are dynamic structures, whose pectin composition varies according to the developmental and functional stages and in response to external factors. Gall inducers change the functional profiles of their host organs, and herein, we explore how stem cell walls respond to gall development, particularly in the nutritive tissues consumed by the lepidopteran larva. The pectin composition of the non-galled stems of Marcetia taxifolia (Melastomataceae) in primary and secondary growth and of Lepidoptera stem galls in distinct stages of development were studied by immunocytochemistry. During the development of the stems of M. taxifolia, the changes in protein and pectin composition suggest that young stems are growing and elongating with the help of extensins, arabinogalactan-proteins (AGPs), and homogalacturonans (HGs). In the galls, the predominance of galactans indicates changes in the pectin composition, allowing cell wall stiffness in hyperplasic tissues. The chewing stimuli of the Lepidoptera induce the synthesis of galactans, arabinans, and HGs in nutritive cells, allowing the cell wall flexibility during the hyperplasic process and the porosity necessary for the translocation of water and nutrients toward the gall chamber.